2019
DOI: 10.1001/jamaoto.2019.2725
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia After Primary Transoral Robotic Surgery With Neck Dissection vs Nonsurgical Therapy in Patients With Low- to Intermediate-Risk Oropharyngeal Cancer

Abstract: for the MD Anderson Head and Neck Cancer Symptom Working Group IMPORTANCE A major goal of primary transoral robotic surgery (TORS) for oropharyngeal cancer is to optimize swallowing outcomes by personalized treatment based on pathologic staging. However, swallowing outcomes after TORS are uncertain, as are the outcomes compared with nonsurgical options. OBJECTIVES To estimate rates of acute dysphagia and recovery after TORS and to compare swallowing outcomes by primary treatment modality (TORS or radiotherapy)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
91
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(101 citation statements)
references
References 43 publications
7
91
1
1
Order By: Relevance
“…Oropharyngeal squamous cell carcinoma (SCC) may be treated in the primary setting with both surgical and nonsurgical strategies, with comparable oncologic and functional outcomes between primary radiation and transoral robotic surgery (TORS). [6][7][8][9] In the salvage setting after radiation or chemoradiation, the treatment of oropharyngeal SCC becomes far more complex. Reirradiation is typically not an optimal choice due to intolerable toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Oropharyngeal squamous cell carcinoma (SCC) may be treated in the primary setting with both surgical and nonsurgical strategies, with comparable oncologic and functional outcomes between primary radiation and transoral robotic surgery (TORS). [6][7][8][9] In the salvage setting after radiation or chemoradiation, the treatment of oropharyngeal SCC becomes far more complex. Reirradiation is typically not an optimal choice due to intolerable toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Transoral robotic surgery is a well-established treatment strategy for oropharyngeal cancers with excellent oncological and functional outcomes. [1][2][3][4][5] Further applications have been described for supraglottic, [6][7][8][9] partial, 10 and total laryngectomies [11][12][13] with promising initial results.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have used the MD Anderson Dysphagia Inventory (MDADI), 10,11,13,14 Functional Oral Intake Scale, 15 Eating Assessment Tool (EAT-10), 16 Performance Status Scale-Head and Neck (PSSHN), 15,17,18 and Functional Oral Swallowing Scale. 19 Comparative studies have demonstrated similar patient rated severity of dysphagia at 3 and 6 months for both definitive CRT and TORS, 10,14 however, potentially superior swallowing function for CRT at 12 months. 11 In those patients where adjuvant treatment can be avoided, TORS can result in minimal dysphagia, depending on baseline function and tumor classification.…”
Section: Introductionmentioning
confidence: 99%
“…22 Despite this, only four studies have examined swallowing in the OPC TORS population using instrumental assessment. 10,[13][14][15] These cohorts involved patients with a mean age of 55 to 61 years, majority males and varied participant numbers ranging between 10 and 257. To the best of our knowledge, a study reporting on acute dysphagia after TORS evaluated by FEES has not been published.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation